Kesejahteraan Psikologis Anggota Kepolisian Bag Logistik Polresta Surakarta - Ima Nia Uliasari; Sri Ernawati (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
A aw enforcement agency and public servant in Indonesia, the police must demonstrate good performance. In order to maintain and improve police performance, one way is to improve psychological well-being. This is because the better the psychological well-being, the better the performance. Psychological well-being can conceptually be influenced by demographic factors (age, gender, socio-economic status and culture). The author then developed these demographic factors into career development perception variables (socio-economic). Based on this, this study aims to see the psychological well-being of members of the Surakarta Police's logistics unit. The subjects of this study were 7 members of the logistics unit. The results of the study found that the psychological well-being of members of the logistics unit had a positive and significant influence on psychological well-being.